1995
DOI: 10.1002/mpo.2950240605
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of I‐Leucovorin Rescue Following High‐Dose Methotrexate for Osteosarcoma

Abstract: High-dose methotrexate with leucovorin rescue (HDMTX-LCV) is an important component of regimens used in the treatment of osteosarcoma. As of this writing the commercially available form of leucovorin is a racemic mixture of d- and l-diastereoisomers; the l-isomer is the active component. This study describes the efficacy and safety of l-leucovorin in HDMTX-LCV regimens. Fifteen patients with osteosarcoma who were enrolled into or treated according to Pediatric Oncology Group protocols 8759 and 8651 received l-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Supportive of this notion, previous studies have shown that FA can preserve the gain of bone density in rabbits treated with MTX in a similar dosing to rheumatoid arthritis treatment (Laurindo et al, 2003) and that FA can limit the extent of MTX-induced bone growth arrest in mice (Iqbal et al, 2003). Previously, clinical usefulness of FA has been shown in reducing toxicity in soft tissues (Goorin et al, 1995;Peters et al, 2000) from MTX chemotherapy in children. Interestingly, chemotherapy with FA supplementation preferentially kills neoplastic over non-neoplastic cells in vitro, and it selectively spares normal bone marrow hematopoietic cells and intestinal epithelial in animals from MTX adverse effects (Chow and Rubin, 1998).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Supportive of this notion, previous studies have shown that FA can preserve the gain of bone density in rabbits treated with MTX in a similar dosing to rheumatoid arthritis treatment (Laurindo et al, 2003) and that FA can limit the extent of MTX-induced bone growth arrest in mice (Iqbal et al, 2003). Previously, clinical usefulness of FA has been shown in reducing toxicity in soft tissues (Goorin et al, 1995;Peters et al, 2000) from MTX chemotherapy in children. Interestingly, chemotherapy with FA supplementation preferentially kills neoplastic over non-neoplastic cells in vitro, and it selectively spares normal bone marrow hematopoietic cells and intestinal epithelial in animals from MTX adverse effects (Chow and Rubin, 1998).…”
Section: Discussionmentioning
confidence: 76%
“…The current study characterized cellular and structural damage caused by short-term MTX treatment in the proximal tibial growth plate cartilage, metaphyseal bone and bone marrow, and examined potential effects of supplementary treatment with one clinically used agent (folinic acid (FA)) in protecting the bone growth mechanisms during MTX chemotherapy. FA is sometimes administered as an antidote following MTX to decrease toxicity in soft tissues (Goorin et al, 1995;Peters et al, 2000). Although two previous studies had reported that FA has some protective effects on growing skeleton against MTX damage on the macroscopic level (Iqbal et al, 2003;Laurindo et al, 2003), it remains to be investigated how FA protects the cellular mechanisms for bone formation during MTX chemotherapy.…”
mentioning
confidence: 98%
“…Relationship between MTXAUC and MTX plasma concentrations at 24 h after MTX infusion patients with fast renal elimination of MTX at risk of inferior clinical outcome [9].Leucovorin rescue, usually started 24 h after the infusion of HDMTX, improves the therapeutic index of MTX [28], and is an important therapeutic tool to avoid severe MTX-associated toxicity such as renal dysfunction, neutropenia and mucositis [29,30]. Although HDMTX is widely used as the backbone for treating patients with PCNSL [1, 2, 6-8, 10, 31], there are still some open issues, including the lack of a uniform dosing regimen [9], the marked interindividual variability in the elimination of MTX [17] and the fact that two retrospective clinical studies have suggested that MTX dose intensity in patients with PCNSL may be important to improve treatment activity [19,20].…”
Section: Figurementioning
confidence: 99%
“…In spite of the therapeutic effectiveness of MTX in cancer treatment and other non‐malignant conditions, its adverse side effects to the soft tissues often result in discontinuation of treatment (Van Ede et al, ; Whittle and Hughes, ). In the clinic, folinic acid (Leucovorin), is administered as part of the MTX treatment regimen in order to alleviate soft tissue toxicities (Goorin et al, ; Van Ede et al, ). Folinic acid (FA) is a derivative of tetrahydrofolic acid and is readily converted to folic acid derivatives without the action of DHFR; thus, in the presence of MTX it enables some purine and pyrimidine synthesis to occur.…”
mentioning
confidence: 99%